A new species of Senegalia (Leguminosae-Mimosoideae) from the Caatinga Domain, Brazil - Terra, Vanessa; Garcia, Flávia Cristina Pinto (Phytotaxa, 2016)
We describe, illustrate and compare Senegalia cearensis, a new Brazilian species of Senegalia from the Caatinga domain in the state of Ceará, with its most morphologically similar species, S. tubulifera. Additionally, we provide an identification key to all Senegalia species similar to S. cearensis occurring in Caatinga domain, and comments on the geographic distribution, flowering and fruiting period of S. cearensis.